Slave trades, kinship structures and women political participation in Africa - Leoné Walters; Carolyn Chisadza; Matthew Clance (African Economic History Network (AEHN), 2021)
We study whether present-day women political participation in sub-Saharan Africa can be linked to the temporary gender ratio imbalances caused by the transatlantic and Indian Ocean slave trades, taking into account pre-existing gender norms influenced by kinship structures. Using individual-level data for 29 sub-Saharan African countries from the latest Afrobarometer surveys, ethnic region kinship and slave trade data, we find that a woman's ethnic region exposure to the transatlantic slave trade is associated with an increase in her likelihood to vote, however, only in non-patrilineal ethnic regions. This effect is mitigated in patrilineal ethnic regions, where women have less decision-making power. This paper contributes to the literature on the contemporary sub-national effects of the slave trades and the historical causes of gender gaps in political participation.
Keywords: 330; Slave Trade; Gender; Africa